Unlocking the secrets of reverse shoulder arthroplasty: A radiological appraisal (Journal of Pakistan Orthopaedic Association, 2024)
Reviewing the literature on radiological evaluation of reverse shoulder arthroplasty (RSA), this paper looks at recent findings. Plain radiographs and computed tomography (CT) scans are among the imaging modalities discussed to assess this procedure's effectiveness. The various radiological assessment methods for glenoid bone loss evaluation, implant position assessment, and early and late potential problem detection are also reviewed in this article. It also goes over the correlations that have been documented between various radiological parameters and clinical outcomes. The study concludes that radiological assessment is a valuable tool for assessing the effectiveness of reverse shoulder arthroplasty and that more research is required to increase its precision.